Fast 4x4 Tchebichef Moment Image Compression - Lang, W.S.; Abu, N.A.; Rahmalan, H. (2009 International Conference of Soft Computing and Pattern Recognition, 2009)
This paper proposes a new approach based on 4×4 discrete orthogonal Tchebichef moment for fast and efficient image compression. The method incorporates a simplified mathematical framework technique using matrices, as well as a block-wise reconstruction technique to eliminate possible occurrences of numerical instabilities at higher moment orders. The comparison between 4×4 Tchebichef moment transform and discrete cosine transform has been done. The results show significant advantages for 4×4 Tchebichef moment in terms of its error reconstruction and average bit-length of Huffman codes.